In Silico Prediction of Binding Affinities of Hybrid Molecules of Benzothiazole cross-linked with Hydroxamic acid by certain linkers - yazen alqaysi; Shakir M. Alwan; Ashour H. Dawood (College of Pharmacy / Mustansiriyah University, 2024)
New hybrid molecules of Benzothiazole cross-linked with hydroxamic acid through an amino acid or aminoalkanoic acid are suggested. All the synthesized hybrid molecules (2A-E) were subjected to molecular docking to evaluate their binding affinities with histone deacetylase enzyme (HDAC8, PDB ID: 1T69) and recorded lower ΔG (-8.117, -6.322, -8.16, -7.939, - 9.46, respectively) than Vorinostat (suberoylanilide hydroxamic acid, SAHA), as the reference ligand, which recorded a much less value of -5.375, using the Maestro software (Schrödinger, version 2022-1).  Moreover, compound 2E, which is Benzothiazole-p-amino benzoic acid-hydroxamate has recorded the lowest binding score (-9.460). This may indicate that this compound is the most active hybrid molecule. There were no violations from Lipinski's rule and all the synthesized hybrid molecules comply with all parameters.  SwissADME server was employed for the in silico molecular docking for prediction of the physicochemical and ADME properties of the investigated compounds.  All hybrid molecules showed low possible passive oral absorption and no penetration into BBB. The hybrid molecules 2B and 2D may be considered as P-gp substrates. SAHA does not inhibit any of the CYP enzymes used in this study, while, the hybrid molecules 2B, 2D and 2E have shown possible inhibitory activities.